Early-life immunomodulation by carvacrol delivered in ovo in broiler chickens - Mila M.Y. Meijer; Henry van den Brand; Chiara Palmieri; Shahram Niknafs; Asad A. Khaskheli; Eugeni Roura (Poultry Science)
ABSTRACT: In the first 2 wk after hatching, broiler chickens are vulnerable to enteric pathogens due to underdeveloped gastrointestinal and immune systems. Carvacrol has been reported to improve digestive and immune functions. This study aimed to optimize immune development of broiler chickens by delivering carvacrol in ovo. Effects of 2 in ovo treatments delivered at embryonic day (E)17.5 (saline or carvacrol) were evaluated at 3 stages (E19.5, hatch, and d 14 posthatch). Hatchability, performance parameters, lymphoid organ and yolk sac weights were determined. Histomorphology assessment was performed for jejunal samples at hatch and bursa of Fabricius samples at hatch and d 14. Gene expression of immune-relevant genes was determined for jejunal, bursal, and yolk sac samples over time. At hatch, BW was 0.85% lower (P = 0.02) after in ovo carvacrol delivery compared to the controls. Interactions between in ovo treatment and age were found for gene expression. At hatch, carvacrol treatment resulted in lower expression of proinflammatory cytokines IL-8 and IFN-γ in the yolk sac compared to the controls (P = 0.05 and < .001, respectively) suggesting a potential role for carvacrol-mediated immune modulation. At d 14, carvacrol treatment led to lower expression of proinflammatory cytokine IL-6 in the bursa compared to the controls (P = 0.002). In ovo carvacrol delivery led to bursal histomorphometric changes, including a larger cortex in the bursal follicles (P = 0.03), and a higher cortex/medulla ratio (P = 0.04) compared to the controls, indicating increased B-cell stimulation and maturation. Main effects were found for carvacrol treatment in the jejunum, with overall higher expression of proinflammatory mediators IL-1β and NF-κB, and anti-inflammatory IL-10 compared to the controls (P = 0.04, 0.02, and 0.02 respectively) from E19.5 to d 14. Age-related main effects showed various alterations in expression dynamics of immune-related genes across all tissues over time. Our findings suggest changes in immune parameters occur as the chicken develops, but these mostly do not interact with in ovo carvacrol treatment. In ovo carvacrol treatment alters immune activity of broiler chickens independent of age.